Corporate Social Responsibility and Forest and Other Land Uses (FOLU) Policies as an Emission Reduction Strategy - Arrizal, Nizam Zakka; Taufiq, Abd Rohman (MultiTech Publisher, 2024)
The role of humans, organizations and government policies contributes to dealing with various problems in Indonesia, one of which is environmental pollution. This is the background to the birth of Corporate Social Responsibility (CSR). CSR is a business commitment to operate legally and contribute to improving the quality of life and partnership responsibility of the company, employees and their families, government, local community and wider community. CSR can be carried out by empowering local communities in a real way which has an impact on environmental sustainability. Government policies related to sustainability commitments are important in order to support the success of sustainable forest management for climate change mitigation. For this reason, more strategic government policies are needed in order to realize this action. This type of research is juridical-normative by examining the provisions and juridical aspects related to legal issues with secondary data from the literature as a primary source by conducting a search of laws and regulations, the results of the research show that CSR policies create companies that are accountable to the environment, this is will support the Indonesia Forest and Other Land Use (FOLU) Net Sink 2030 mitigation actions.